Educational Psychology - Abdullah, Berivan Mohammed Ahmed; Dabney-Fekete, Ilona D.; Ceglédi, Tímea (Central European Journal of Educational Research, 2025)
Bibliography of the reviewed book: Santrock, J. W. (2018). Educational Psychology (6 Ed). McGraw-Hill Education.